The use of large and small ruminant in selected experimental surgery - Mohamed Yusof, Loqman; Goriman Khan, Mohd Azam Khan; Ibrahim, Rashid (Universiti Putra Malaysia Press, 2004)
Large and small ruminants were used in a number of research studies and surgical exercises in UPM. In the studies, various surgical techniques and approaches were used as outlined in the study design. Either local or general anaesthesia technique was applied in the surgical procedures. A part from the clinical aspect the understanding of the anatomy and distinctive physiological features of the animals is important when conducting such experiments, to yield good experimental results.